The Power of Words in Disney’s Songs - Mohar, Tjaša; Gramc, Martina (Music with a Message: Words, Music and Propaganda 2, 2025)
Popular media, especially music and movies, can play a significant role in shaping people’s beliefs and attitudes. Animated movies produced by the Walt Disney Company, which blend animation and music, serve as particularly powerful tools for conveying values and ideologies, since their targeted audience consists of young viewers, who are highly impressionable and can easily internalize Disney’s worldviews, which are often criticized. This chapter examines how ideological messages are interwoven into the song lyrics in a selection of Disney’s animated movies. By analysing the song lyrics, we aim to disclose the various ideological subtexts that they contain and define why they are problematic. The analytical part is divided into three sections: the first section investigates examples of song lyrics that promote American values; the second takes a closer look at gender stereotyping and promotion of romantic love, while the third discloses racial political incorrectness.